2014
DOI: 10.4028/www.scientific.net/amr.984-985.3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Effect of High Pressure Coolant with Various Cutting Speed and Feed on Surface Roughness in Cylindrical Turning of AISI 1060 Steel Using Carbide Insert

Abstract: Providing sufficient provisions to transfer heat from the work-tool interface is a key to improve tool life and surface integrity. With the conventional flood cooling system where the coolant is directed towards the work-tool interface at very low pressure, there are possibilities for the coolant to get heated up and produce vapors which in turn insulates the cutting zone from the coolant. This reduces the purpose of coolant. Supplying coolant at very high pressure and very high velocity may provide the best c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This increases the radial and tangential forces. An increase in force for higher feed rates was seen by other researchers as well [2,24,23]. With around 10% contribution, cutting speed is the second most significant factor.…”
Section: Forcesmentioning
confidence: 54%
See 1 more Smart Citation
“…This increases the radial and tangential forces. An increase in force for higher feed rates was seen by other researchers as well [2,24,23]. With around 10% contribution, cutting speed is the second most significant factor.…”
Section: Forcesmentioning
confidence: 54%
“…Machining parameters (cutting speed, feed rate, and depth of cut), tool parameters (tool material, microgeometry, and macro-geometry) and chemical composition of the work material are the most common factors that affect the machinability of a material [2][3][4][5]. It has been reported that with an increase in cutting speed there is a reduction in the cutting forces, whereas increasing the feed increases the cutting forces [2,4]. In addition to the machining parameters, tool geometries like edge preparation and nose radius also have a higher influence on the forces and residual stress distribution [3].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the surface roughness of a machining operation can be controlled by optimizing the cutting parameters [23] or by changing the geometrical features of the tool like corner radius and wiper facet [24]. However, the work-material-dependent properties like composition, mechanical, and metallurgical properties also play a role in determining the surface roughness.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Among these variables, the micro-geometry of the tool plays a major role in determining the stress distribution and tool wear [1]. In terms of cutting parameters, increasing the cutting speed improves the surface finish and decreases the forces, whereas increasing the feed rate reduces surface quality and increases the force [2,3].…”
Section: Introductionmentioning
confidence: 99%